1998
DOI: 10.1001/jama.280.6.521
|View full text |Cite
|
Sign up to set email alerts
|

Incident <EMPH TYPE="ITAL">Chlamydia trachomatis</EMPH> Infections Among Inner-city Adolescent Females

Abstract: Context.-Adolescents are at highest risk for infection with Chlamydia trachomatis, an important preventable cause of pelvic inflammatory disease and subsequent tubal factor infertility in US women. Current guidelines for delivery of adolescent primary care services recommend yearly chlamydia screening for those adolescent females considered to be at risk.Objectives.-To describe the epidemiology of prevalent and incident chlamydia infection among adolescent females to assess the appropriate interval for chlamyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
2
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(137 citation statements)
references
References 48 publications
3
130
2
2
Order By: Relevance
“…This rate is comparable to rates of asymptomatic infection among previously examined sexually active populations. [8][9][10][11][12][13][14][15] Urine-based screening was easy to integrate into emergency department service delivery and was well accepted by the emergency department client population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate is comparable to rates of asymptomatic infection among previously examined sexually active populations. [8][9][10][11][12][13][14][15] Urine-based screening was easy to integrate into emergency department service delivery and was well accepted by the emergency department client population.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Previous screening studies have demonstrated high prevalence rates of asymptomatic chlamydial infection in family planning centers, adolescent health facilities, detention centers, school-and community-based clinics, and military settings. [8][9][10][11][12][13][14][15] The emergency department represents another health care access site for identifying persons with asymptomatic STIs. Many persons at risk for STIs use emergency departments as a primary source of health care.…”
mentioning
confidence: 99%
“…In turn, these simplified specimen collection procedures now permit highly sensitive [1][2][3][4] testing for treatable sexually transmitted diseases (STDs) in nonclinical sites and at other locations of convenience where at-risk persons might congregate. [5][6][7][8] A growing literature supports the association between drugs (including alcohol) and high-risk sexual behavior. [9][10][11][12] Most of these studies, however, focused on persons who were actively using drugs.…”
Section: Introductionmentioning
confidence: 99%
“…An individual was classified as having an incident infection if a positive test with either a prior negative test or a prior positive at least 30 days earlier had been documented within the study period. 2 All cases identified as positive received treatment. A positive result at the first visit was not considered an incident case.…”
Section: Gendermentioning
confidence: 99%